Patient and public involvement facilitators: Could they be the key to the NHS quality improvement agenda?. (5th February 2020) - Todd, Sarah; Coupland, Christine; Randall, Raymond
Abstract: Objective: Research into patient and public involvement (PPI) has not examined in detail patient and public involvement facilitators' (PPIFs) roles and activities. This study analysed PPIFs' roles using qualitative data gathered from three different UK health‐care organizations. Design: Thematic analysis was used to examine cross‐sectional data collected using a mixed‐methods approach from three organizations: a mental health trust, a community health social enterprise and an acute hospital trust. The data set comprised of 27 interviews and 48 observations. Findings: Patient and public involvement facilitators roles included the leadership and management of PPI interventions, developing health‐care practices and influencing quality improvements (QI). They usually occupied middle‐management grades but their PPIF role involved working in isolation or in small teams. They reported facilitating the development and maintenance of relationships between patients and the public, and health‐care professionals and service managers. These roles sometimes required them to use conflict resolution skills and involved considerable emotional labour. Integrating information from PPI into service improvement processes was reported to be a challenge for these individuals. Conclusions: Patient and public involvement facilitators capture and hold information that can be used in service improvement. However, they work with limited resources and support. Health‐care organizations need to offer more practical support to PPIFs in their efforts to improve care quality, particularly by making their role integral to developing QI strategies.